PEMANFAATAN MULTIMEDIA SEBAGAI MEDIA DAKWAH - Andi Hasriani (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2012)
The development of information and communication tehcnologies have entered all areas of life. The discovery of the symbols as a language of communication, the invention of printing, radio, television, computers and the internet contribute potentially to Islamic preaching. The convergence of such media is easily found in the society today. For example, a laptop connected to the internet can access to television broadcasting, radio, nespapers, magazines, and social networks like Facebook, Twitter, and others. This development should be paid attention for the sake of Islamic preaching to provide a variety of resources, especially human rexources in this area. This multimedia facilities has also been used to preach by making sites of Islamic preaching, which can utilised at any time and in very beneficial for the people and the development of Islamic preaching.